Case report of ipsilateral humeral shaft fracture and shoulder dislocation treated by closed reduction followed by intramedullary nailing. (October 2021) - Hara, Maya; Yamazaki, Ken
Abstract: Combined humeral shaft fracture and shoulder dislocation injury is rare. Consequently, there are no standard treatment protocols for this injury. We present a case of a 33-year-old man who slipped off a motorcycle and incurred a right humeral shaft fracture and right shoulder dislocation. We performed closed reduction of the shoulder followed by intramedullary nailing. The protocol is different from most in existing papers and results in a good prognosis. However, gentle reduction is essential to avoid iatrogenic neurovascular damage.